Adaptive Medium Access Control Protocol for Wireless Body Area Networks. (17th March 2014) - Javaid, N.; Ahmad, A.; Rahim, A.; Khan, Z. A.; Ishfaq, M.; Qasim, U.
Wireless Body Area Networks (WBANs) are widely used for applications such as modern health-care systems, where wireless sensors (nodes) monitor the parameter(s) of interest. Nodes are provided with limited battery power and battery power is dependent on radio activity. MAC protocols play a key role in controlling the radio activity. Therefore, we present Adaptive Medium Access Control (A-MAC) protocol for WBANs supported by linear programming models for the minimization of energy consumption and maximization of dataflow. Our proposed protocol is adaptive in terms of guard band assignment technique and sleep/wakeup mechanism. We focus on specific application to monitor human body with the help of nodes which continuously scan body for updated information. If the current value is within normal range, nodes do not try to access channel. However, if the current value rises or falls beyond the permissible range, nodes switch on their transceiver to access channel. Moreover, A-MAC uses TDMA approach to access channel and well-defined synchronization scheme to avoid collisions. Furthermore, we conduct a comprehensive analysis supported by MATLAB simulations to provide estimation of delay spread. Simulation results justify that the proposed protocol performs better in terms of network lifetime and throughput as compared to the counterpart protocols.